Measurement of fish freshness: Flow cytometry analysis of isolated muscle mitochondria. (30th March 2022) - Soret, Méline; Bouchendhomme, Tiffanie; Cleach, Jérôme; Jouy, Nathalie; Crola Da Silva, Claire; Devin, Anne; Grard, Thierry; Lencel, Philippe
Highlights: Using flow cytometry, mitochondria provided an excellent marker of fish freshness. Just after the fish has died, isolated mitochondria maintained high potential. In the medium term after death, isolated mitochondria lost their potential. More than 3 days after death, isolated mitochondria always re-polarizable after addition of substrates. From 7 days after death, isolated mitochondria were strongly depolarized. Abstract: Mitochondria are real sensors of the physiological status of tissues. After the death of an animal, they maintain physiological activity for several days. This activity is highly dependent on the availability of nutrients in the tissue. In this study, flow cytometry was used to measure the membrane potential of mitochondria isolated from European seabass ( Dicentrarchus labrax ) red muscle stored in ice for seven days in order to characterize fish freshness. Two probes, TMRM and Rhodamine 123, were used to measure mitochondrial potential. During the first few days (D0 to D3), isolated mitochondria maintained high potential, and then lost their potential (from D3 to D5), but were always re-polarizable after addition of substrates (glutamate, malate and succinate). From D7, the mitochondria were more strongly depolarized and were difficult to repolarize by the substrates. Using flow cytometry, we demonstrated that mitochondria were an excellent marker to confirm seabass freshness.